The association between Chinese eye exercises and myopia in children and adolescents: A systematic review and meta-analysis - Tang, Jie; Pei, Yifei; Wang, Jingjing; Yan, Na; Luo, Yunjiao; Zhou, Wen; Wang, Xiaojuan; Wang, Wei (Frontiers in Public Health, 2023)
Objective: To Summarize the relevant evidence on the association between eye exercises and myopia in children and adolescents in China. Methods: The meta-analysis pooled the results of 12 studies involving a total of 134201 participants. A further 5 studies (no OR for myopia as outcome and meeting inclusion criteria) were reported in the systematic review. We searched PubMed, Web of Science, CNKI, Wan Fang and reference lists of retrieved studies. Association estimates were pooled using random-effects meta-analyses. Pooled odds ratios (ORs) and 95% confidence intervals (CIs) for eye exercises and myopia from a meta-analysis. Results: After standardized the reference values, a pooled OR of univariate analysis showed a 24% reduction in myopia in children and adolescents who performed eye exercises (OR=0.76; 95% CI: 0.62-0.89). After adjusting the covariates, a pooled OR of multiple logistic analysis for myopia (OR=0.87; 95%CI: 0.72-1.02) shows that there is no significance between eye exercises and myopia. However, in subgroup studies of multivariate analysis, the large sample (OR=0.84;95%CI: 0.74-0.94) and Chinese database (OR=0.80; 95%CI: 0.67-0.93) subgroup showed modest protective effects. In addition, five studies in the systematic review also evaluated the risk of myopia events, Chinese eye exercises had a modest protective effect on myopic control, but the incorrect performance and attitude of eye exercises posed negative effects to their eyesight health. Conclusion: Chinese eye exercises had a modest protective effect on myopic control, but considering the incorrect performance and attitude of eye exercises have significant influence on the effect of eye exercises, the effect of eye exercises may not be enough to prevent the progress of myopia for a long time, and more standardized eye exercises needed to be conducted.